2014
DOI: 10.1039/c4cc02179g
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic–fluorescent–plasmonic nanomaterials: towards integrated three-component photoactive hybrid nanosystems

Abstract: Silica-coated gold nanorods functionalized with grafted fluorescent and photochromic derivatives were synthesized and characterized. Spectroscopic investigations demonstrated that cross-coupled interactions between plasmonic, photochromic, and fluorescence properties play a major role in such nanosystems, depending on the thickness of the silica spacer, leading to multi-signal photoswitchability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…These concepts are developed quantitatively in the following sections. We note that enhanced backconversion of cPC has been achieved with plasmonic enhancement from gold nanoparticles and shown to be dependent on the distance from the nanoparticle surface 21,22 .…”
Section: Design Of Psqd Nanoparticles With Photochromic Acceptorsmentioning
confidence: 80%
“…These concepts are developed quantitatively in the following sections. We note that enhanced backconversion of cPC has been achieved with plasmonic enhancement from gold nanoparticles and shown to be dependent on the distance from the nanoparticle surface 21,22 .…”
Section: Design Of Psqd Nanoparticles With Photochromic Acceptorsmentioning
confidence: 80%
“…Also, gold nanorods can be coated with silica and functionalized with grafted fluorescent and photochromic derivatives (Figure 19 bottom). [204] Spectroscopic investigations demonstrated that cross-coupled interactions between plasmonic, photochromic, and fluorescence properties play a major role in such nanosystems, depending on the thickness of the silica spacer, leading to multi-signal photoswitchability.…”
Section: Figure 12mentioning
confidence: 99%
“…The black curve is for the sample with GNRs 1, red curve for GNRs 2, and green curve for GNRs 3 concentration in the dried polymer is calculated to 9 × 10 −2 mol L −1 . Moreover, in other study, the samples were considered as consisting of isolated nanoparticles whether they were in solution [11,26] or deposited on a glass substrate [25]. They never exhibit coupling SPR modes which are present in our case.…”
Section: Resultsmentioning
confidence: 98%
“…In such cases, they observed the same reversible modifications, namely a broadening and a shifting of the main SPR band. Only few works report about the coupling of gold nanorods and photochromic molecules [26]. In such study, both the transverse and the longitudinal SPR modes were modified by the photochromic process in the wavelength range where these SPR bands overlap the absorption band of the colored form of the photochromic compound.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation